2019
DOI: 10.1039/c9py00879a
|View full text |Cite
|
Sign up to set email alerts
|

Role of pendant side-chain length in determining polymer 3D printability

Abstract: The effect of polymer side chain on extrusion-based direct-write 3D printing and rheology is examined. Longer side chain length improves printability at ambient temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Most recently, Joy and co‐workers systematically studied the relationship between saturated, aliphatic pendant side chain length and 3D printability. [ 66 ] It was found that an increase of side chain length could reduce viscosity and enable extrusion at low temperature and pressure, while long chain length could adversely affect the ability to retain a 3D printed shape. In another work, the commonly overlooked issue of possible degradation in thermoplastic aliphatic polyesters during FFF process was studied.…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Joy and co‐workers systematically studied the relationship between saturated, aliphatic pendant side chain length and 3D printability. [ 66 ] It was found that an increase of side chain length could reduce viscosity and enable extrusion at low temperature and pressure, while long chain length could adversely affect the ability to retain a 3D printed shape. In another work, the commonly overlooked issue of possible degradation in thermoplastic aliphatic polyesters during FFF process was studied.…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
“…The use of dynamic bonds which undergo reversible breaking, exchange and reformation could be utilized to modify the printability of polymers as well as imparting various advanced functions. [ 41–58,62–67,59,68,60,69,70,72,61,73,71,82,86–88,74–81,83–85,89–133,244,258 , …”
Section: Summary and Perspectivementioning
confidence: 99%
“…Thus the shear rate dependency of our vitrimer confirmed feasibility of FDM‐based printing. [ 6 , 45 ] Next, as illustrated in Figure 5 , we generated vitrimer filaments by a mono‐screw‐equipped extruder and the extruded filament was found to show the same shape memory effects as the films did (Figure 5b ). We then applied the filaments to a portable 3D pen to create artwork (Movie S2 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in an extrusion‐based polymer 3D printing, printability can be assessed based on 1) pressure‐driven flow, that is, ability to extrude as continuous filaments; 2) formation of beads with stable geometry, that is, ability to retain the printed shape; 3) ability to form free‐hanging filaments, that is, bead functionality; and 4) ability to form structurally sound and dimensionally accurate printed parts. [ 247,248 ] These criteria are expected to vary for 3D printing techniques such as VP and SLS with different part building strategies and process requirements. Therefore, printability is generally related to the printing material's intrinsic and extrinsic features (structure and properties), its ability to resist formation of defect during printing, and processing.…”
Section: Improving Printability Of Polymeric Materialsmentioning
confidence: 99%